Incomplete joint side tear of the subscapularis tendon with a small fragment in an adolescent tennis player: a case report - Kato Soki; Funasaki Hiroki; Kan Iwao; Yoshida Mamoru; Kasama Kentaro; Marumo Keishi (BMC, 2012)
Abstract Case In this case report, we presented the case of an adolescent tennis player with avulsion injury of the subscapularis tendon of the right shoulder. Patients A 17-year-old right-hand-dominant male tennis player visited our hospital complaining of pain in the anterior aspect of the right shoulder. We performed X-ray and three-dimensional computed tomography (3D-CT) and magnetic resonance imaging (MRI) scans for the diagnosis. Results Plain radiographs did not reveal the presence of lesion; however, 3D-CT and MRI scans showed a small bony fragment located between the humeral head and the glenoid of the scapula and a high-intensity area of the subscapularis tendon. He was subsequently diagnosed with incomplete joint side tear of the subscapularis tendon with a small bony fragment. Subsequently, we performed arthroscopic excision of the bony fragment and repair of the subscapularis tendon. Conclusions This case highlighted the presence of an injury with minor trauma associated with repeated tennis strokes in a skeletally immature patient.